Penyelidikan keberkesanan dan kefahaman penduduk wilayah persekutuan Labuan terhadap dakwah Islam - Mohd Noh Dalimin; Ridzwan Abdul Rahman; Saini Ag. Damit; Ahmad Tarmizi Abd. Rahman; Mohd. Azri Ibrahim; Mohamad Shaukhi Mohd Radzi; Issraq Ramli; Abdul Said Ambotang; Ferlis Bahari; Md. Razali Saibin (Universiti Malaysia Sabah, 2007)
No Abstract